Purification, crystallization and preliminary X-ray diffraction analysis of adenosine triphosphate sulfurylase (ATPS) from the sulfate-reducing bacterium Desulfovibrio desulfuricans ATCC 27774 - Gavel, Olga Yu (2019)
Native zinc/cobalt-containing ATP sulfurylase (ATPS; EC 2.7.7.4; MgATP:sulfate adenylyltransferase) from Desulfovibrio desulfuricans ATCC 27774 was purified to homogeneity and crystallized. The orthorhombic crystals diffracted to beyond 2.5 Å resolution and the X-ray data collected should allow the determination of the structure of the zinc-bound form of this ATPS. Although previous biochemical studies of this protein indicated the presence of a homotrimer in solution, a dimer was found in the asymmetric unit. Elucidation of this structure will permit a better understanding of the role of the metal in the activity and stability of this family of enzymes.